Alpha-Mangostin Activates MOAP-1 Tumor Suppressor and Mitochondrial Signaling in MCF-7 Human Breast Cancer Cells - Simon, Samson Eugin; Lim, Hui Sin *; Fairen, Angelin Jayakumar *; Tan, Ee Wern *; Tan, Kuan Onn * (Wiley Open Access, 2022)
α-Mangostin, one of the major constituents of Garcinia mangostana, has been reported to possess several biological activities, including antioxidant, anti-inflammatory, antibacterial, and cytotoxic activities associated with the inhibition of cell proliferation and activation of apoptosis. However, the cellular signaling pathway mediated by α-mangostin has not been firmly established. To investigate the cellular activities of α-mangostin, human cancer cells, MCF-7 and MCF-7-CR cells, were treated with α-mangostin to measure the cellular responses, including cytotoxicity, protein-protein interaction, and protein expression. Cancer cells stably expressed Myc-BCL-XL and HA-MOAP-1 were also included in the studies to delineate the cell signaling events mediated by α-mangostin. Our results showed that the apoptosis signaling mediated by α-mangostin involves the upregulation of endogenous MOAP-1, which interacts with α-mangostin activated BAX (act-BAX) while downregulating the expression of BCL-XL. Moreover, α-mangostin was found to induce BAX oligomerization, the release of mitochondrial cytochrome C, and activation of caspase in MCF-7 cells. In overexpression studies, MCF-7 cells and spheroids stably expressed HA-MOAP-1 and Myc-BCL-XL exhibited differential chemosensitivity toward α-mangostin in which the stable clones expressing HA-MOAP-1 and MYC-BCL-XL were chemosensitive and chemoresistant to the apoptosis signaling events mediated by α-mangostin, respectively, when compared to untreated cells. Together, the data suggest that the cytotoxicity of α-mangostin involves the activation of MOAP-1 tumor suppressor and its interaction with act-BAX, leading to mitochondria dysfunction and cell death.